Single-Molecule Real-Time and Illumina-Based RNA Sequencing Data Identified Vernalization-Responsive Candidate Genes in Faba Bean (Vicia faba L.) - Yuan, Xingxing; Wang, Qiong; Yan, Bin; Zhang, Jiong; Xue, Chenchen; Chen, Jingbin; Lin, Yun; Zhang, Xiaoyan; Shen, Wenbiao; Chen, Xin (Frontiers in Genetics, 2021)
Faba bean (Vicia faba L.) is one of the most widely grown cool season legume crops in the world. Winter faba bean normally has a vernalization requirement, which promotes an earlier flowering and pod setting than unvernalized plants. However, the molecular mechanisms of vernalization in faba bean are largely unknown. Discovering vernalization-related candidate genes is of great importance for the faba bean breeding. In this study, the whole transcriptome of faba bean buds was profiled by using NGS and SMRT full-length transcriptome sequencing technology. A total of 29,203 high-quality non-redundant transcripts, 21,098 complete CDS, 1,045 lncRNAs, and 12,939 SSRs were identified. Furthermore, 4,044 DEGs were identified through pairwise comparisons. By GO enrichment and KEGG analysis, these differentially expressed transcripts were found to be enriched in binding and transcription factor activity, electron carrier activity, rhythmic process and receptor activity. Finally, 50 putative vernalization-related genes that played important roles in vernalization of faba bean were identified, and we also found that the levels of vernalization-responsive transcripts showed significantly higher expression levels in cold treated buds. The expression of VfSOC1, one of the candidate genes, was sensitive to vernalization. Ectopic expression VfSOC1 in Arabidopsis brought to the earlier flowering. In conclusion, the abundant vernalization-related transcripts identified in this study will provide a basis for future researches on the vernalization and faba bean breeding and established a reference full-length transcriptome for future studies on faba bean.